Personality Traits and Socio-Demographic Factors as Predictors of Succession Planning among Family-Owned Businesses - Uye, Emmanuel Etim; Ogunyinka, Bolanle O.; Okurame, David E. (Jurnal Psikologi Teori dan Terapan, 2024)
Background: The most lasting gifts a business could pass on to the next generation is who is next to take over the family-owned business. Little studies have been done on succession plan among family-own business in Nigeria. Objective: This study examines personality traits and socio-demographic factors as likely predictors of succession planning among family-owned businesses in Ibadan metropolis. Cross-sectional survey design using purposive sampling technique was used to sample seven family-owned businesses. Data were collected from 120 participants using standardized questionnaires. Zero-order correlation statistics and multiple regression analysis were utilized to analyze the collected data. Results: The result revealed that personality traits jointly predicted succession planning among participants. Also, age, education, gender, job status, marital status, and work experience jointly predicted succession planning among participants. Finally, marital status and work experience independently predicted succession planning. Conclusion: Personality traits and socio-demographic factors were robust predictors of succession planning among family-owned businesses in Ibadan. The novelty of this finding is that succession planning is rarely studied among family-owned businesses.